Revenue recognition at TSA, Inc.—A roller coaster ride - Chandra, U.; Dutta, Saurav; Marcinko, D. (American Accounting Association, 2018)
This case chronicles revenue recognition practices at TSA, Inc. from 1997 to 2002. As growth in TSA’s revenue declined, the company’s revenue recognition practices became more aggressive. In 2002, TSA’s incoming auditors re-evaluated its revenue recognition policies and restated its financial statements for three prior years. The case provides a real-world situation with complex contracts through which students can improve their understanding of the five-step revenue recognition process under ASC 606, which became effective in fiscal year 2018 for most public entities. Further, it is a rich setting in which to illustrate the judgment and complexity involved in revenue recognition. The case provides students with an opportunity to approach revenue recognition from different perspectives—that of corporate accountant, manager, external auditor, and investor—and is designed for use in Intermediate Accounting as well as in capstone accounting courses at both the undergraduate and graduate levels.